2021
DOI: 10.1002/mrm.29014
|View full text |Cite
|
Sign up to set email alerts
|

Training data distribution significantly impacts the estimation of tissue microstructure with machine learning

Abstract: Purpose Supervised machine learning (ML) provides a compelling alternative to traditional model fitting for parameter mapping in quantitative MRI. The aim of this work is to demonstrate and quantify the effect of different training data distributions on the accuracy and precision of parameter estimates when supervised ML is used for fitting. Methods We fit a two‐ and three‐compartment biophysical model to diffusion measurements from in‐vivo human brain, as well as simulated diffusion data, using both tradition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 44 publications
5
42
0
Order By: Relevance
“…By simply matching the q‐space sampling parameters in the biophysical models to the desired q‐space, such training data can be easily generated. Moreover, biophysical models provide a convenient method to generate training data that span a wide range of parameters such as diffusivities and volume fractions and fiber orientations, whereas, the parameter span of data‐driven training may be clustered around certain ranges 24 . This convenient framework also allows for re‐training the neural network to learn a new q‐space manifold by simply modifying the q‐space sampling parameters in the biophysical models.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…By simply matching the q‐space sampling parameters in the biophysical models to the desired q‐space, such training data can be easily generated. Moreover, biophysical models provide a convenient method to generate training data that span a wide range of parameters such as diffusivities and volume fractions and fiber orientations, whereas, the parameter span of data‐driven training may be clustered around certain ranges 24 . This convenient framework also allows for re‐training the neural network to learn a new q‐space manifold by simply modifying the q‐space sampling parameters in the biophysical models.…”
Section: Theorymentioning
confidence: 99%
“…Moreover, biophysical models provide a convenient method to generate training data that span a wide range of parameters such as diffusivities and volume fractions and fiber orientations, whereas, the parameter span of datadriven training may be clustered around certain ranges. 24 This convenient framework also allows for re-training the neural network to learn a new q-space manifold by simply modifying the q-space sampling parameters in the biophysical models. One disadvantage of previous data-driven DL methods is the generalizability of the learned information.…”
Section: Brief Review Of Qmodelmentioning
confidence: 99%
“…Neural networks (Golkov et al, 2016), polynomial regression (Reisert et al, 2017), or random forest (Palombo et al, 2020) have provided useful results in different dMRI applications. The ML approach has been applied to estimate SM parameters by (Reisert et al, 2017), and followed by more recent works (Coelho et al, 2021a;Gyori et al, 2021;de Almeida Martins et al, 2021). Irrespective of the implementation, all these works concluded that ML estimation alone is unable to resolve SM parameter degeneracies, and that a sufficiently rich acquisition protocol is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the main focus will be improving the distribution of the training data. There are some investigations [13,14] talking about how the distribution of the data could influence the machine learning. However, this issue is hardly discussed in the context of MOR.…”
Section: Introductionmentioning
confidence: 99%